Pengembangan Modul Anatomi dan Fisiologi Tubuh Manusia Berbasis Case Method untuk Mahasiswa Jurusan Biologi - Siti Aisyah Siti; Melva Silitonga; Syahmi Edi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to develop and produce a case-based Human Anatomy and Physiology module that is suitable for use as a learning resource for students. This research is a research and development (R&D) study using the Five-Stage Level 1 model, with 84 Biology Education students, class of 2021, as the target subjects. Data collection techniques and instruments used were expert validation sheets and lecturer and student response questionnaires. The research data were analyzed using feasibility analysis techniques based on the feasibility of the material, design, language, and learning. The study concluded that the case-based Human Anatomy and Physiology module was deemed feasible based on assessments from material expert validators (4.35), design expert validators (4.00), and learning expert validators (4.29), and was deemed quite feasible based on assessments from language expert validators (3.78). The lecturers and students of the Biology Education Study Program generally gave good responses (4.36 and 4.14) to the case-based Human Anatomy and Physiology module. Keywords: Human Anatomy and Physiology, Case Method, Five-Stage Model, Module.